Activation of peroxymonosulfate by BiFeO3 microspheres under visible light irradiation for decomposition of organic pollutants. Issue 83 (9th September 2015) - Chi, Fangli; Song, Biao; Yang, Bin; Lv, Yaohui; Ran, Songlin; Huo, Qisheng
<x xml:space="preserve">Abstract</x> BiFeO3 microspheres were firstly used to activate peroxymonosulfate under visible light irradiation for oxidation and degradation of organic pollutants.